PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN WANITA PASANGAN USIA SUBUR (PUS) TENTANG DETEKSI KANKER SERVIKS PADA WALI MURID TK ISLAM AL MUJAHIDIN CILACAP - Intarti, Wiwit Desi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
In Indonesia, each year detected more than 15,000 cases of cervical cancer, and about as many as 8000 cases of which ended with the death.the purpose of this research is to know the influence of health education against the level of knowledge of women of fertile age couples cervical cancer detection on about caregivers TK Al Mujahideen Cilacap. The research method used was a quasi experimental design research with nonrandomized pre – post test control group design this design which gives the pretest (pengawamatan) first before given intervention, then conducted posttest (observation end) after the intervention. The sample in this research totalled 30 subject research. Data analysis using statistical test of Paired-Samples t-test or the paired t test. The results of the calculation shows that the average respondent knowledge before given health education was 9.90 and average knowledge of respondents increased after health education be given 13. Based on the test t (paired test) obtained the value t calculate registration-11 with 39 and df p-value of 0.001. so a null hypothesis (Ho) was rejected and the working hypothesis (Ha) received, namely there is the influence of health education against the level of knowledge of women of fertile age couples (PUS) cervical cancer detection on about caregivers TK Al Mujahideen Cilacap. Key words: Health Education, knowledge, cervical canser